Secado natural de yuca para la alimentacion animal: Una nueva agroindustria en Colombia - Ospina, B.; Gómez G., Guillermo G.; Best, R. (International Center for Tropical Agriculture, 1982)
A collaborative project of the Colombian Integrated Rural Development Program (DRI) and CIAT, aimed at establishing small agroindustrial firms to produce dry cassava on the Atlantic Coast of Colombia, is described. It began with the installation of a pilot plant for natural drying of cassava, with the collaboration of a group of 15 farmers. This plant operated on an exptl. basis in 1981 to obtain information about the efficiency of the process under the conditions existing on the Colombian Atlantic Coast and to determine the product`s acceptability by the animal feed industry. In 1982, during the project`s 2nd phase, the pilot plant was operated semicommercially to obtain data on production costs; likewise, it showed the economical and technical feasibility of the process. In 1983, the 3rd phase began, consisting in the replication of the project in other cassava-producing areas of the region. In 1984 and 1985, the project grew considerably, with 20 drying plants functioning in 1984 and 36 in 1985. To establish small-scale natural cassava drying plants, the following requisites are essential: (1) selection of a processing technology that can be assimilated, controlled, and easily managed by farmers; (2) implementation of integrated programs of processing, production, and commercialization that reduce the risks and increase net incomes of farmers; and (3) provision of institutional support that is adequate in terms of technical assistance, credit facilities, management and fiscal training, and of advice in the formation and consolidation of cooperative and associative groups for agricultural production. (AS-CIAT)